The larva of Lepidostoma doehleri Malicky 1976 (Trichoptera: Lepidostomatidae) with notes on ecology and a key to larvae for species of the genus in Greece - Karaouzas, Ioannis; Waringer, Johann (Zootaxa, 2016)
The hitherto unknown larva of Lepidostoma doehleri Malicky 1976 is described. The diagnostic features of the species are listed and illustrated, and some information on its ecology is included. In addition, diagnostic characters for the larvae of the known Lepidostoma species occurring in Greece are provided.